TINDAK PIDANAPENYALAHGUNAAN DATA PRIBADI ORANG LAIN PADA PEMINJAMAN ONLINE - Ibrahim Fikma Erdisy (Legalita, 2020)
Criminal Law policy Against the act of falsifying the personal identity of others when analyzed using Article 35 jo. Article 51 paragraph (1) UU ITE. Law Number 11 of 2008 concerning Electronic Information and Transactions as amended by Law Number 19 of 2016 concerning Electronic Information and Transactions, there are elements that whoever commits an act of manipulation, creation, alteration, removal, destruction electronic information or electronic documents intentionally, whether against the law or not, can be sentenced to a maximum of 12 imprisonment and a maximum fine of 12,000,000,000 (twelve billion rupiah), for now there is no special regulation that regulates the criminal act of falsifying data in Indonesia. online loans therefore still use the applicable Positive Law.